2016
DOI: 10.1021/acsami.6b04807
|View full text |Cite
|
Sign up to set email alerts
|

Study of Gallium Oxide Nanoparticles Conjugated with β-Cyclodextrin: An Application To Combat Cancer

Abstract: Bioactive nanomaterials, namely, gallium oxyhydroxide GaO(OH), also surface-conjugated GaO(OH) with a giant sugar molecule β-cyclodextrin (CD), have been prepared through a simple wet chemical route such that the same could be suitably used in biomedical diagnostics as well as therapeutic applications. Several physical methods were used for their characterization: powder X-ray diffraction pattern of GaO(OH) NPs for their grain size determination, optical spectroscopic absorption (UV-vis and FT-IR), and fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…In the spectrum of GaCurNPs, most of the peaks corresponding to the curcuminic structure were observed with a slight shift in the wavenumber and intensity due to the interaction with GaO(OH). 36 No characteristic bands of GaO(OH) were observed in the FT-IR spectrum possibly due to overlapping and chemical modification. 37 Unlike in curcumin, the O–H stretching of enolic and phenolic parts merged to form a broad peak centered at 3330 cm –1 .…”
Section: Resultsmentioning
confidence: 99%
“…In the spectrum of GaCurNPs, most of the peaks corresponding to the curcuminic structure were observed with a slight shift in the wavenumber and intensity due to the interaction with GaO(OH). 36 No characteristic bands of GaO(OH) were observed in the FT-IR spectrum possibly due to overlapping and chemical modification. 37 Unlike in curcumin, the O–H stretching of enolic and phenolic parts merged to form a broad peak centered at 3330 cm –1 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we confirmed that the diffraction patterns on Figure 1 can be assigned to the orthorhombic GaOOH structure and are in agreement with literature reports. 25 …”
Section: Results and Discussionmentioning
confidence: 99%
“…However, an increase in the hydrodynamic size distributions was observed due to the oxidation of LMNPs to form elliptical-shaped Ga oxide hydroxide (GaOOH) nanorods 48 h after production (Figure b). The oxidation of LMNPs is an alternative to conventional sol–gel technique for producing GaOOH nanorods with an organic coating . We discovered that the formation of oxide nanorods could be inhibited by passivating the LMNP surface with trisodium citrate antioxidant (Figure b), thereby significantly improving stability.…”
Section: Grafting Liquid Metal Particles With Polymersmentioning
confidence: 99%